PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Anggraini Saputri; Sri Harmuli; Sintia Hepi Andini; Risdalina; Destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of implementing the Problem Based Learning (PBL) model on improving the mathematics learning motivation of fifth-grade students at SD Negeri 14/I Sungai Baung. The background of this research is based on the low level of student motivation in mathematics which is evident from the lack of active participation, low enthusiasm in completing assignments, and passive attitudes during lessons. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 14 students in class V A. Data collection instruments included a learning motivation questionnaire, teacher and student observation sheets, and documentation. The results showed that the implementation of the Problem Based Learning model had a positive impact on students' motivation to learn mathematics. In the first cycle, the average motivation score was 61,4 with a classical completeness rate of 57.14%. After improvements in the second cycle, the average motivation score increased to 80, with a classical completeness rate of 85.71%. Based on these results, it can be concluded that the Problem Based Learning model is effective in increasing elementary school students’ motivation to learn mathematics.